2021
DOI: 10.1029/2020jc016727
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurements of the Malvinas Current Velocity Structure

Abstract: The cold Malvinas Current (MC) is one of the main circulation patterns in the southwestern South Atlantic Ocean (Peterson & Whitworth III, 1989). This current originates as a branch of the Antarctic Circumpolar Current (ACC) (Provost et al., 1996), rounds east of the Falklands/Malvinas Islands, and flows northward along the continental slope of South America (Figure 1) (Willson & Rees, 2000). The MC follows the Subantarctic Front (SAF), one of three main fronts of the ACC in the Drake Passage (Barre et al., 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Since the latitude of northernmost MC penetration is also associated with a sharp increase in SST, we compared the gADT derived location of the MC with the location of the maximum along‐slope SST gradient (gradySST). To calculate gradySST, we averaged the SST between the 300 and 1800 m isobaths, where the core of MC is located (Frey et al., 2021). We applied a 1‐degree x 1‐degree low‐pass filter to the SST data to eliminate noise and calculated the along‐slope gradient of SST.…”
Section: Methodsmentioning
confidence: 99%
“…Since the latitude of northernmost MC penetration is also associated with a sharp increase in SST, we compared the gADT derived location of the MC with the location of the maximum along‐slope SST gradient (gradySST). To calculate gradySST, we averaged the SST between the 300 and 1800 m isobaths, where the core of MC is located (Frey et al., 2021). We applied a 1‐degree x 1‐degree low‐pass filter to the SST data to eliminate noise and calculated the along‐slope gradient of SST.…”
Section: Methodsmentioning
confidence: 99%
“…The MC is an equivalent‐barotropic current that flows along the Patagonian continental slope with surface velocities of the order of 60 cm/s (Figure 1b). Observations suggest that the MC is organized in two narrow jets at 45°S (Frey et al., 2021; Piola et al., 2013). Poli et al.…”
Section: Introductionmentioning
confidence: 99%
“…The MC is an equivalent-barotropic current that flows along the Patagonian continental slope with surface velocities of the order of 60 cm/s (Figure 1b). Observations suggest that the MC is organized in two narrow jets at 45°S (Frey et al, 2021;Piola et al, 2013). Poli et al (2020) showed that shelf break trapped waves modulate the intensity of the inner jet -SAF-N branch-while slow waves propagating from the Malvinas Escarpment and the Drake Passage modify velocities in the main jet-SAF-M branch-(Figure 2a).…”
mentioning
confidence: 99%
“…Liu et al, 2019;Pätsch et al, 2017). The transport rates of boundary and slope currents, for instance, are underestimated in our low-res runs but become more energetic in the high-res simulation, for example, with increases of the Malvinas Current along the PS by 20% (high-res mean 20.7 Sv at 45°S, literature 20-25 Sv by Frey et al [2021]), the NWES slope current by 35% (high-res mean 2.4 Sv at 58°N, literature 1-4 Sv by Marsh et al [2017] and Clark et al [2021]), and shelf break upwelling velocities by a factor of 4. On the shelves, the general patterns of the circulation and seasonal stratification are comparatively similar in both configurations (Figure A4), though become more structured and confined in high-res.…”
Section: Discussionmentioning
confidence: 64%
“…The transport rates of boundary and slope currents, for instance, are underestimated in our low‐res runs but become more energetic in the high‐res simulation, for example, with increases of the Malvinas Current along the PS by 20% (high‐res mean 20.7 Sv at 45°S, literature 20–25 Sv by Frey et al. [2021]), the NWES slope current by 35% (high‐res mean 2.4 Sv at 58°N, literature 1–4 Sv by Marsh et al. [2017] and Clark et al.…”
Section: Discussionmentioning
confidence: 75%